2020
DOI: 10.3164/jcbn.20-10
|View full text |Cite
|
Sign up to set email alerts
|

New colorimetric method with bromocresol purple for estimating the redox state of human serum albumin

Abstract: Oxidative damage results in protein modification and is observed in many diseases, such as heart failure and renal insufficiency. Human serum albumin is an index of oxidative change and is conventionally measured using high-performance liquid chromatography (HPLC). Although this method is more sensitive than the colorimetric method, it is time-consuming for clinical practice and the sera must be stored at –80°C before analysis. To overcome these limitations, in the present study we developed a new reagent for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Muramoto et al developed a modified BCP method [ 55 ], where the difference in binding affinities was resolved through facilitating conversion of reduced ALB to oxidized ALB by adding sodium dodecyl sulfate and 5,5′-dithiobis(2-nitrobenzoic acid) to the BCP reagent. A recent study by Yoshihiro et al is notable as they applied the modified BCP method to the determination of serum ALB redox state [ 56 ]. Namely, serum samples are reacted with BCP both in the presence and absence of sodium dodecyl sulfate and 5,5′-dithiobis(2-nitrobenzoic acid) under a condition where BCP sensitively reacts with oxidized ALB.…”
Section: Analytical Chemistry Of Serum Alb Redox Statementioning
confidence: 99%
“…Muramoto et al developed a modified BCP method [ 55 ], where the difference in binding affinities was resolved through facilitating conversion of reduced ALB to oxidized ALB by adding sodium dodecyl sulfate and 5,5′-dithiobis(2-nitrobenzoic acid) to the BCP reagent. A recent study by Yoshihiro et al is notable as they applied the modified BCP method to the determination of serum ALB redox state [ 56 ]. Namely, serum samples are reacted with BCP both in the presence and absence of sodium dodecyl sulfate and 5,5′-dithiobis(2-nitrobenzoic acid) under a condition where BCP sensitively reacts with oxidized ALB.…”
Section: Analytical Chemistry Of Serum Alb Redox Statementioning
confidence: 99%
“…The total measurement time was 15 min per sample. (8,9) Statistical analysis. Continuous variables were expressed as the mean and SD, while categorical variables were expressed as the percentage (%).…”
Section: Measurement Of Hna and Human Mercaptalbumin (Hma)mentioning
confidence: 99%
“…(7) Recently, novel colorimetric method with bromocresol purple was also reported. (8) To this end, we recently reported that HNA is a useful marker for evaluating the redox state in humans, (9) and we established a reliable and less timeconsuming method for measuring HNA. (10)(11)(12) At present, many studies on oxidative stress have sought its potential roles in the pathogenesis of various diseases.…”
mentioning
confidence: 99%
“…A handful of studies have explored alternative approaches using simple dye-based assays [ 3 , 23 , 24 ]. These can be adapted for high-throughput formats, such as multi-well plate readers and clinical chemistry analyzers.…”
Section: Introductionmentioning
confidence: 99%
“…These can be adapted for high-throughput formats, such as multi-well plate readers and clinical chemistry analyzers. For example, Yoshihiro and co-workers developed a simple colorimetric assay to measure the percentage of HNA using bromocresol purple (BCP) dye [ 24 ]. This assay takes advantage of the fact that the BCP dye, traditionally used to measure total serum albumin concentrations, shows greater colorimetric absorbance when it reacts with HNA than with HMA [ 25 ].…”
Section: Introductionmentioning
confidence: 99%